Stress-related factors Pregnant Women in the Working Area of the Limboto Health Center, Gorontalo Regency - Sitti Nur Fajria D. Latief; Nurdiana Djamaluddin; Siti Hajar Salawali (Universitas Muhammadiyah Palu, 2026)
Stress in pregnant women can be influenced by various factors, including family support, age, parity and maternal knowledge. Stress is a psychological response that arises when an individual faces a situation that is perceived to be beyond their ability or difficult to deal with. The purpose of this study is to find out the factors related to stress in pregnant women in the working area of the Limboto Health Center, Gorontalo Regency. The research method uses a correlative analytical quantitative research design with a cross sectional approach. The population in this study amounted to 121 respondents with a sample size of 93 respondents calculated using a significance level of 5%, using a non-probability sampling technique, namely accidental sampling. The instruments in this study used a family support questionnaire, a maternal knowledge questionnaire, and a PDQ (Prenatal Distress Questionnaire) stress questionnaire. The results showed that there was a significant relationship between factors such as age, family support, parity, maternal knowledge and stress in pregnant women in the working area of the Limboto Health Center, Gorontalo Regency with a p-value = < 0.05 using the chi square correlation test and the spearman rank correlation test. With this research, it is hoped that it can be an effort to prevent stress in pregnant women through providing support and knowledge to prevent adverse effects on mothers and babies.